Profil Kinerja Guru Agama Hindu Yang Sudah Bersertifikat Pendidik - I Made Wiguna Yasa; I Komang Wisnu Budi Wijaya (Kamaya: Jurnal Ilmu Agama, 2020)
This research aims to describe the performance of educator certified Hinduism teachers at the junior high schools in Tabanan Regency. This research is descriptive research. The population of this study were all educator certified Hinduism teachers at the junior high schools in Tabanan Regency. Sampling was done by using saturated sampling technique. The research instrument that used was a teacher performance sheet questionnaire consisting of 33 (thirty three) items. The instrument has been tested for validity and reliability before use. The research data were analyzed descriptively. The results of the reaserch indicate that: 1) the performance of educator certified Hinduism teachers at the junior high schools in Tabanan Regency is high with an average score of 72.00 and 2) as many as 2.16% of Hinduism teachers have very high performance; 82.61% are in the high criteria and 15.21% are in the sufficient category.